Berwirausaha Kopi di Masa Pandemi Coronavirus Disease 2019 di Kecamatan Medan Labuhan - Anshar, Muhammad; Fahmi, Teuku; Siregar, Fandi Alfiansyah (JURNAL AKUNTANSI DAN MANAJEMEN, 2021)
The Medan Mayor's policy of issuing a regional regulation on large-scale social restrictions forced the coffee shop entrepreneur to close down his business for several months. The purpose of this study was to determine the strategy of coffee shop owners in entrepreneurship during the Covid 19 pandemic, to find out the entrepreneurial communication mechanisms carried out by coffee shop owners and to find out the obstacles faced by coffee shop owners. This research is a qualitative descriptive study using survey and observation methods and data collection techniques are measured using interviews and documentation. The central and local governments have not provided assistance to coffee shop owners in the form of injections of funds to stay afloat and be entrepreneurial during the Covid 19 pandemic. The Medan city government should make joint policies with business actors in the city of Medan in general, especially coffee shop owners  who have limited capital and coffee shop owners must have breakthrough ideas and new innovations in entrepreneurship to face the Covid 19 pandemic that has not ended.